Sur 1905 - Girault, René; Keenan, E.L.; Baynac, Jaques; Engelstein, Laura; Yassour, Avraham (Paris : Champ Libre, 1974)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Russische Revolutie 1905; Rusland